Mycetoma management and clinical outcomes: the Mycetoma Research Center experience - Musa, Esraa Abdelgadir; Abdoon, Iman Hassan; Bakhiet, Sahar Mubarak; Osman, Bashier; Abdalla, Safa A; Fahal, Ahmed Hassan (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2023)
Mycetoma is a chronic granulomatous inflammatory disease that affects the cutaneous and subcutaneous tissues, leading to gruesome complications if not treated early. As a neglected disease, it has received scant attention in developing curable drugs. Mycetoma treatment is still based on expert opinions in the absence of guidelines. This descriptive, cross-sectional, hospital-based study aimed to determine and assess the disease treatment outcomes observed at Mycetoma Research Center, Sudan. In this study, 75% of patients had eumycetoma, all of whom were treated with itraconazole and 37.4% underwent surgical excision, while 25% of the patients had actinomycetoma, 99.2% of whom were treated with a combination of cotrimoxazole and amoxicillin-clavulanate. The cure rate was 12.7% and 14.3% for patients with eumycetoma and actinomycetoma, respectively. Only 6.1% of eumycetoma patients underwent amputation. Remarkably, no patient with actinomycetoma underwent an amputation. Small lesions (OR=10.09, p<0.001) and good follow-up (OR=6.81, p=0.002) were positive predictors of complete cure. In terms of amputation, history of surgical recurrence at presentation (OR=3.67, p=0.020) and presence of grains (OR=7.13, p=0.012) were positive predictors, whereas small lesions were negative predictors (OR=0.06, p=0.009). Treatment of mycetoma was suboptimal, with a low cure rate despite a long treatment duration. Complete cure has a significant association with small lesions and good follow-up.